Perceived Stress Moderates the Impact of Internalizing Symptoms on Family Functioning in Early Adolescence. (November 2020) - Simpson, Emily G.; Vannucci, Anna; Lincoln, Courtney R.; Ohannessian, Christine McCauley
This study investigates the impact of early adolescent internalizing symptoms on family functioning for girls and boys, as moderated by perceived stress. Surveys were administered to 1, 344 middle school students (11-14 years; 51% girls; 51% non-Hispanic White) in the fall of 2016 (T1) and 6 months later in the spring of 2017 (T2). For boys, depressive symptoms predicted less family conflict only among those with low stress. For girls, depressive symptoms predicted less adolescent-mother communication among those with low stress, but more communication among those with high stress. Also for girls, anxiety predicted more family cohesion in girls with low stress, but less cohesion among those with high stress. Finally, anxiety predicted less adolescent-father communication only among girls with low stress. Findings underscore the complex role that perceived stress plays when considering the impact of internalizing symptoms on family functioning in early adolescent girls and boys.